Do advanced glycation end products contribute to food allergy? - Smith, P. K.; Venter, C.; O’Mahony, L.; Canani, R. Berni; Lesslar, O. J. L. (Frontiers in Allergy, 2023)
Sugars can bind non-enzymatically to proteins, nucleic acids or lipids and form compounds called Advanced Glycation End Products (AGEs). Although AGEs can form in vivo, factors in the Western diet such as high amounts of added sugars, processing methods such as dehydration of proteins, high temperature sterilisation to extend shelf life, and cooking methods such as frying and microwaving (and reheating), can lead to inordinate levels of dietary AGEs. Dietary AGEs (dAGEs) have the capacity to bind to the Receptor for Advanced Glycation End Products (RAGE) which is part of the endogenous threat detection network. There are persuasive epidemiological and biochemical arguments that correlate the rise in food allergy in several Western countries with increases in dAGEs. The increased consumption of dAGEs is enmeshed in current theories of the aetiology of food allergy which will be discussed.